ANALISIS PERUBAHAN TEMPERATUR UDARA 2004-2010 UNTUK MEMPREDIKSI TEMPERATUR UDARA 2011-2014 DI KALIMANTAN SELATAN - Rampan, Reko Ary; Siregar, Simon Sadok; Munir, MIftahul (Jurnal Fisika FLUX, 2013)
Abstrak: Nowadays, green house gas was increased which caused air temperature ofsurface arise, one of them is carbon dioxide (CO2), CO2 is part of green house gas whichis strong enough to absorb infrared wave, but if CO2 concentration is too high it wouldmake earth warming at the surface. The objective of the research is to made airtemperature changes modeling ( ), air temperature modeling ( ) in 2004-2010based on CO2 concentration trend and also to predict air temperature modeling 2011-2014 in Kalimantan Selatan. The research is literature study by using ( ) modeling.The modeling is made to known value of air temperature changes modeling since 1750based on CO2 concentration trend which used to modeling air temperature ( ) in2004-2010 based on CO2 concentration trend and also its predict. Data that was used isair temperature of observation in 7 point in 2004-2010 and CO2 concentration data ofIndonesia in 2004-2010. Result of the research shown that air temperature changesmodeling in 2004-2010 based on CO2 concentration trend was changed since 1750 isabout 1,53-1,68ÂºC, model shown that air temperature modeling in 2004-2010 based onCO2 concentration trend about 26,72-26,77ÂºC and air temperature modeling in 2011-2014 based on CO2 concentration trend about 26,772â26,795ÂºC.Keywords: Temperature, Carbon Dioxide (CO2), Kalimantan Selatan